Functional results of total-knee arthroplasty versus medial unicompartmental arthroplasty: two-year results of a randomised, assessor-blinded multicentre trial - Knifsund, Jani; Niinimaki, Tuukka; Nurmi, Heikki; Toom, Alar; Keemu, Hannes; Laaksonen, Inari; Seppänen, Matti; Liukas, Antti; Pamilo, Konsta; Vahlberg, T; Äärimaa, Ville; Mäkelä, KT (BMJ open, 2021)
ObjectiveThe primary objective of the trial was to assess the clinical effectiveness of medial unicompartmental knee arthroplasty versus total knee arthroplasty in patients with isolated medial osteoarthritis of the knee.DesignProspective, randomised, 2 years, assessor-blind, multicentre, superiority trial.SettingThe patients were enrolled between December 2015 and May 2018 from the outpatient clinics of three public high-volume arthroplasty hospitals (Finland).ParticipantsWe recruited 143 patients with symptomatic-isolated medial osteoarthritis of the knee needing an arthroplasty procedure. All the patients were suitable for both unicompartmental and total knee arthroplasties. Population was selected as the end-stage-isolated medial osteoarthritis.InterventionsAll patients, randomized 1:1, received a medial unicompartmental arthroplasty or a total knee arthroplasty through a similar midline skin incision. Patients were blinded to the type of arthroplasty for the whole 2 years of follow-up.Main outcome measuresPrimary outcome measure was between-group differences in the Oxford Knee Score (OKS) and secondary outcome Knee injury and Osteoarthritis Score (KOOS) at 2 years postoperatively. The changes within and between the groups were analysed with analysis of variance for repeated measurements.ResultsThe primary outcome was comparable for medial unicompartmental arthroplasty and total knee arthroplasty at 2 years. The mean difference in the OKS between the groups was 1.6 points (95% CI −0.7 to 3.9). In the KOOS subscales, the mean difference between the groups was 0.1 points (95% CI −4.8 to 5.0) for pain, 7.8 points (95% CI 1.5 to 14.0) for symptoms, 4.3 points (95% CI −0.6 to 9.2) for function in daily living, 4.3 points (95% CI −3.0 to 11.6) for function in sports, and 2.1 points (95% CI −4.8 to 9.1) for knee-related quality of life.ConclusionsThe recovery after unicompartmental knee arthroplasty was faster compared with total knee arthroplasty, but unicompartmental arthroplasty did not provide a better patient-reported outcome at 2 years.Trial registration number NCT02481427.